Structural Dynamics of Ultrathin Cobalt Oxide Nanoislands under Potential Control - Stumm, Corinna; Bertram, Manon; Kastenmeier, Maximilian; Speck, Florian D.; Sun, Zhaozong; Rodríguez-Fernández, Jonathan; Lauritsen, Jeppe V.; Mayrhofer, Karl J.J.; Cherevko, Serhiy; Brummel, Olaf; Libuda, Jörg (Advanced Functional Materials, 2021)
Cobalt oxide is a promising earth abundant electrocatalyst and one of the most intensively studied oxides in electrocatalysis. In this study, the structural dynamics of well-defined cobalt oxide nanoislands (NIs) on Au(111) are investigated in situ under potential control. The samples are prepared in ultra-high vacuum and the system is characterized using scanning tunneling microscopy (STM). After transfer into the electrochemical environment, the structure, mobility, and dissolution is studied via in situ electrochemical (EC) STM, cyclic voltammetry, and EC on-line inductively coupled plasma mass spectrometry. Cobalt oxide on Au(111) forms bilayer (BL) and double-bilayer NIs (DL), which are stable at the open circuit potential (0.8 VRHE). In the cathodic scan, the cobalt oxide BL islands become mobile at potentials of 0.5 VRHE and start dissolving at potentials below. In sharp contrast to the BL islands, the DL islands retain their morphology up to much lower potential. The re-deposition of Co aggregates is observed close to the reduction potential of Co2+ to Co3+. In the anodic scan, both the BL and DL islands retain their morphology up to 1.5 VRHE. Even under these conditions, the islands do not show dissolution during the oxygen evolution reaction (OER) while maintaining their high OER activity.
CRIS-Team Scopus Importer:2021-01-22
Keywords: cobalt oxide; electrocatalysis; electrochemical scanning tunneling microscopy; model catalysis; oxygen evolution reaction